Pengaruh Pengetahuan Perpajakan Pelayanan Perpajakan dan Sanksi Pajak Terhadap Kepatuhan Wajibb Pajak Orang Pribadi (Studi KPP Pratama Malang Utara) - Indri Hapsari (e_Jurnal Ilmiah Riset Akuntansi, 2017)
ABSTRACTTax is a source of state income used to finance all state activities and statedevelopment. Because it is very important to maintain and improve. In this study will bediscussed several factors affecting the compulsory habit is "Influence of UnderstandingAgainst Taxation, Tax Service and Tax Sanctions to Taxpayers Compliance" This study aimsto determine the effect of understanding taxation and taxation and both the law of persial andsimultaneous compliance with taxpayers Person in KPP Pratama Malang Utara.Methods of data that use questionnaires measured by Likert scale. The analysismethod used is multiple linear regression analysis.In this study only the knowledge of taxation that affect the compulsory mandatory.For the next researchers are expected to add independent variables of thequestionnaire that is easy to understand by the respondentsKeyword : Taxpayers Compliance, Understanding Against Taxation, tax service, Taxsanctions.